2013
DOI: 10.1038/npp.2013.179
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Dependent Declarative Memory Consolidation—Unaffected after Blocking NMDA or AMPA Receptors but Enhanced by NMDA Coagonist D-Cycloserine

Abstract: Sleep has a pivotal role in the consolidation of declarative memory. The coordinated neuronal replay of information encoded before sleep has been identified as a key process. It is assumed that the repeated reactivation of firing patterns in glutamatergic neuron assemblies translates into plastic synaptic changes underlying the formation of longer-term neuronal representations. Here, we tested the effects of blocking and enhancing glutamatergic neurotransmission during sleep on declarative memory consolidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 70 publications
6
63
0
Order By: Relevance
“…Moreover, Onur et al (2010) and Kuriyama et al (2011) have recently shown that DCS (250 mg and 100 mg single doses) improve declarative and procedural learning, respectively. Feld et al (2013) demonstrated that DCS (175 mg) can enhance sleepdependent declarative memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Onur et al (2010) and Kuriyama et al (2011) have recently shown that DCS (250 mg and 100 mg single doses) improve declarative and procedural learning, respectively. Feld et al (2013) demonstrated that DCS (175 mg) can enhance sleepdependent declarative memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…During retrieval participants also encoded numbers (Feld et al, 2013) to assess whether mefloquine affects learning performance. Sixteen three-digit numbers were presented on a computer screen for two seconds (500 ms ISI) in three random blocks.…”
Section: Control Measures: Number Encoding Sleepiness Vigilance Momentioning
confidence: 99%
“…Preserved sequential firing during replay, as well as the electrophysiological properties of sharp-wave/ripples, suggests that neuronal plasticity emerging during sleep relies on Hebbian processes such as spike timingdependent plasticity (Sadowski et al, 2016). However, blocking AMPA or NMDA receptormediated synaptic signaling, i.e., the foremost neurochemical processes generating such plasticity, does not compromise the contribution of sleep to declarative memory consolidation (Feld et al, 2013), leaving open the question which neuromolecular mechanisms coordinate sleep-induced plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between sleep and memory maintenance has received detailed attention in the last 20 years (Diekelmann & Born, 2010;Rasch & Born, 2013) and there is widespread interest in enhancing this beneficial effect of sleep on memory (Feld & Diekelmann, 2015), e.g., by enhancing neuronal oscillations (Marshall, Molle, Hallschmid, & Born, 2004;Ngo, Martinetz, Born, & Molle, 2013) or externally cueing replay (Rasch, Buchel, Gais, & Born, 2007;Rudoy, Voss, Westerberg, & Paller, 2009) i.e., processes that support sleepdependent memory. We recently demonstrated that the N-methyl-D-aspartate (NMDA) receptor co-agonist D-cycloserine powerfully enhances sleep-dependent declarative memory consolidation when administered before sleep (Feld, Lange, Gais, & Born, 2013). It is however completely unclear, how this enhancement affects the subtle balance of encoding and memory maintenance in the brain (Richards & Frankland, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These findings pose the intriguing question whether the reduction in memories' susceptibility to retro-active interference during sleep is due to a strengthening of the original trace that would be accompanied by enhanced pro-active interference, i.e., whether new memory traces are harder to establish if they overlap with these stronger old memory traces (Osgood, 1948) The oscillatory properties of sleep that support the consolidation process (Staresina et al, 2015) are ideally suited to drive the strengthening of memory traces via long term potentiation (LTP) (King, Henze, Leinekugel, & Buzsaki, 1999), which occurs mainly at glutamatergic synapses and is mediated by NMDA receptors (Malenka & Bear, 2004;Malenka & Nicoll, 1999). Accordingly, we administered D-cycloserine, a drug that supports NMDA receptor activation by binding to its glycine binding site (Sheinin, Shavit, & Benveniste, 2001), to participants after they learned word-pairs, so that peak plasma concentration occurred during the first half of the sleep phase (Feld et al, 2013). Enhancing NMDA receptor activation benefitted the sleep-dependent consolidation specifically of the word-pairs if given during sleep and thus represents the ideal model to test whether memory traces enhanced by sleep introduce detrimental pro-active interference on new learning.…”
Section: Introductionmentioning
confidence: 99%